Relations Between Theology and Natural Sciences in the Context of Education - Śledziewski, Sławomir (Studia Ecologiae et Bioethicae, 2006)
Man, wanting to progress, must educate himself, the sense of attaining education is formed both by „the deeper desire in the human being”, which leads him to reflect on the subject of God and by the will to study natural sciences, which have permanently changed our way of thinking about the world surrounding us and about ourselves. In the process of cognition faith cannot take the place of reason, nor reason the place of faith, these are two ways of arriving at the truth, which must collaborate in agreement with each other, thus education should concentrate on outlining the relation between theology and natural sciences. Such complementing leads to the cognition and fathoming of the truth, and this, besides the attainment of wisdom, is one of the main assumptions of education.